Bacterial Cell Wall Synthesis Inhibition Of Clerodendrum Squamatum Vahl. Phytoconstituents: A Molecular Insight - Marko Jeremia Kalalo; Elly Juliana Suoth; Irma Antasionasti; Sri Sudewi; Billy Johnson Kepe; Fatimawali Fatimawali (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2021)
Bacterial Cell Wall (BCW) is an essential part of bacteria. Defects in BCW may lead to bacterial death due to failure in maintaining pressure and cell integrity or shape. Penicillin-Binding Protein (PBP) 2a, 1, 2, 3, and 4 are proteins responsible for Methicillin-Resistant Staphylococcus aureus (MRSA) cell wall synthesis. MRSA is a hard-to-treat bacteria due to its antibiotic resistance. Clerodendrum squamatum Vahl. leaves (CSVL) are used by North Sulawesi-Indonesian people as a medicinal plant to treat inflammation and to heal wounds. So, the present study aims to explore CSVL potential as inhibitors of MRSA cell wall synthesis using in silico approach. CSVL phytoconstituents were analyzed using Gas Chromatography-Mass Spectroscopy (GC- MS), and the chemical structures were retrieved from PubChem and docked to PBP2a, PBP1, PBP2, PBP3, and PBP4 using Pyrx-Vina. The toxicity profile of the phytoconstituents was also calculated. The results showed that CSVL interacts with PBPs with a variety of types of bonding, dominated by hydrogen bonds. The toxicity prediction showed that CSVL has a safe toxicity profile. CSVL can be a good anti-MRSA candidate due to its molecular interactions with BCW synthesis proteins.Keywords: MRSA, antibiotic resistance, medicinal plant, PBPs